Diseño y Control de Orientación para un Sistema Estabilizador de Tres Grados de Libertad - Mireles Jr. Medrano, Alan (2019)
This article presents the design and control of a gimbal robot that moves freely throughout three axes. It shows the development of the robot fully from a geometric representation of the movements that affect the system with backup from the changes made over the reference frames, to the 3D modeling and the construction process of the physical assembly. Various experiments were designed to apply PID system controller. In terms of real time execution, the robot presents a limit on movement degrees and the maximum weight it can withstand, although the results were satisfying regarding the application of the stabilization of a video camera.